STANDARDIZED HIGHER ORDER THINKING SKILLS’ ASSESSMENT IN ENGINEERING MECHANICS: A TRADITIONAL LITERATURE REVIEW AND FUTURE RESEARCH DIRECTIONS - Salma Maharani; Riyan Arthur; Soeprijanto Soeprijanto (Jurnal Eduscience)
Purpose – This study aims to examine the need to develop assessment instruments for higher-order thinking skills in teaching Engineering Mechanics in Vocational High Schools under the Construction and Property Technology Expertise Program and explore directions for future research.